2007
DOI: 10.1002/bmc.777
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative LC/MS/MS method and in vivo pharmacokinetic studies of vitexin rhamnoside, a bioactive constituent on cardiovascular system from hawthorn

Abstract: A simple and accurate liquid chromatography coupled with tandem mass spectrometry method was developed for determination and in vivo pharmacokinetic studies of vitexin rhamnoside in rat plasma. After protein precipitation using methanol, the analytes were separated by a Luna C(18) column with an isocratic elution and analyzed by mass spectrometry in multiple reaction monitoring mode using the respective negative ion at m/z 577.2-293.0 for vitexin rhamnoside and m/z 593.2-413.0 for internal standard (IS) vitexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…These findings, suggest not only a higher biodisposition in plasma but also that L7G remains for a longer period of time in the organism. These data are in accordance with previous works regarding the plasma pharmacokinetics of similar compounds, such as vitexin 2''-O-rhamnoside, vitexin 4''-O-glucoside, luteolin 3'-O-glucuronide, apigenin 7-O-glucuronide and acacetin 7-O-glucuronide [28,30,42]. As for the L3'S, it was already reported as being a major ISO metabolite in rats [43].…”
Section: Pharmacokinetics Of Cymbopogon Citratus Infusion In Rats Aftsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings, suggest not only a higher biodisposition in plasma but also that L7G remains for a longer period of time in the organism. These data are in accordance with previous works regarding the plasma pharmacokinetics of similar compounds, such as vitexin 2''-O-rhamnoside, vitexin 4''-O-glucoside, luteolin 3'-O-glucuronide, apigenin 7-O-glucuronide and acacetin 7-O-glucuronide [28,30,42]. As for the L3'S, it was already reported as being a major ISO metabolite in rats [43].…”
Section: Pharmacokinetics Of Cymbopogon Citratus Infusion In Rats Aftsupporting
confidence: 92%
“…High recovery of administered vitexin 4''-O-glucoside and 2''-O-rhamnoside in faeces indicated that the efficient absorption of these molecules from the gastrointestinal tract of rats was low. In fact, it was reported that vitexin 2''-O-rhamnoside has limited gastrointestinal absorption with an oral bioavailability of only 3.57% [28,30]. A recent work investigated the pharmacokinetic and excretion profile of Swertia pseudochinensis extract after its oral administration to rats and determined three secoiridoid glycosides and three flavonoid glycosides in plasma, bile, urine and faeces [25].…”
Section: Introductionmentioning
confidence: 99%
“…No studies in this area on human tissue appear to have been conducted to date. The pharmacodynamic profile of hawthorn extracts has been examined in animal studies,[2930] but no studies appear to have been performed on human subjects.…”
Section: Constituents and Their Mechanisms Of Actionmentioning
confidence: 99%
“…Studies with the C ‐linked dihydrochalcone aspalathin from rooibos revealed that it is absorbed as intact C ‐glucoside from the small intestine in humans and pigs 6, 37, 38. Liang et al identified the intact vitexin rhamnoside in plasma after its oral administration to rats 39. Thus, the intestinal absorption of flavan‐3‐ol C ‐glycosides is as well considered to be possible.…”
Section: Discussionmentioning
confidence: 99%